Kinetics of cellular component in inflammatory response induced by different stimuli in the swim bladder of pacu, Piaractus mesopotamicus Holmberg 1887 (Characidae) - Bozzo, F. R.; Moraes, J. R. E.; de Moraes, Flavio Ruas; Pereira, G. T.; Tavares-Dias, M.; Onaka, E. M. (Blackwell Publishing, 2007)
The present study assessed the kinetics of cell accumulation at the site of inflammation induced by thioglycolate, Escherichia coli lipopolysaccharide (LPS) and heat-inactivated Aeromonas hydrophila, in the pacu, Piaractus mesopotamicus (Characidae), swim bladder. A quantitative, as well as qualitative, assessment was done of all the cells present in the exudate at 6, 24, and 48 h (n = 8) after inoculation of inflammatory agents. The results show that the thioglycolate was the irritant to induce higher total inflammatory cell accumulation when compared to the control group, 6 h after insult (P < 0.05). Inoculation of heat-inactivated Aeromonas hydrophila induced progressive accumulation of total inflammatory cells, with cell number peaking after 24 h and being significantly higher than observed in the other groups (P < 0.05). Injection of LPS also induced greater cell accumulation when compared to the control group (P < 0.05), although in lower numbers than those induced by the other two irritants. All irritants injected induced significantly greater accumulation of lymphocytes and thrombocytes when compared to the control group (P < 0.05).